Characteristics Of Human Resource Competencies On The Successful Implementation Of The Regional Government Information System (Sipd) In Improving The Quality Of Financial Reports At Uptd Pelayanan Sosial Dinas Sosial Provinsi Sumatera Utara - Rizki, Dinar; Agustina, Ika; Sihotang, Iin Sri Ayu; Rahmadini, Najwa; Ramadhani, Annisa; Irawan (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
The purpose of this study is to examine the influence of human resource competency on the success of implementing the Regional Government Information System (SIPD) and its impact on the quality of financial reports at Uptd Pelayanan Sosial Dinas Sosial Provinsi Sumatera Utara. This research was conducted at Uptd Pelayanan Sosial Dinas Sosial Provinsi Sumatera Utara.The research employed a descriptive qualitative approach, with data collection techniques including in-depth interviews, participant observation, and documentation studies. The research informants consisted of structural officials, SIPD operators, planning staff, and senior employees who are directly involved in the implementation of SIPD. The findings indicate that technical competence, system knowledge, and work attitudes have a significant influence on the successful implementation of SIPD. The main obstacles identified include the lack of specific training, limited digital infrastructure, differences in perceptions among operators, and resistance from senior employees toward new technologies. The implementation of SIPD has not yet been fully optimized, as there are still discrepancies in data input, errors in planning logic, and a low level of understanding of the system workflow. Therefore, strategies to strengthen human resource competencies are required, including intensive training programs, continuous technical assistance, standardization of standard operating procedures (SOPs), and the enhancement of digital culture. This study confirms that the quality of human resources is a fundamental foundation for the success of digital government initiatives at the regional level.